Efficiency determinants of Malaysian conventional and Islamic banks - A 5-year period study - Arulanandam, Benedict Valentine*; Selvan, Christo (Niali Field Consultancy and Training (NFCT), 2019)
The growth of conventional and Islamic banking in Malaysia has been commendable and has brought positive impact into the overall economic growth for Malaysia. The efficiency of Malaysian banks has always been a point of debate. Based on certain studies by Awan (2009), Bader, et al. (2008), and Mokhtar (2006), draws the need to further deliberate on the area of banks efficiency, especially the efficiency of conventional and Islamic banks in Malaysia. This study visits three fundamental questions, which are; what is the efficiency for Islamic and conventional banks in Malaysia between the period 2009 to 2013?; does the efficiency of conventional banking supersedes that of Islamic banking in Malaysia during the same period?; and what are the factors influencing the efficiency of conventional and Islamic banks in Malaysia? Hence the purpose of this study is to address these three research questions between the 5-year period, which represents the period after the 2008 global financial crisis, revealing the required actions by regulators and industrial experts to further improve the banking landscape in Malaysia.